2019
DOI: 10.4028/www.scientific.net/amm.887.527
|View full text |Cite
|
Sign up to set email alerts
|

Visual Impairment, Adaptation Luminance, and Glare: An Empirical Investigation

Abstract: Visually impaired people primarily rely on their remaining vision. Unfavorable lighting conditions can further hamper this remaining vision. In this context, the present contribution mainly focuses on the evaluation of the visual performance of visually impaired and normally sighted individuals under different lighting conditions. To investigate the visual performance empirically, we developed a test involving different adaptation luminance values. A monitor with adjustable brightness facilitated various tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Moreover, about one-third of the employees were dissatisfied with artificial light and the overall quality of light, and two out of five of those having a window were dissatisfied with their view. Hauck et al , 48 in their test comparing the visual performance of visually impaired and normal-sighted individuals, found that special lighting conditions were required by most people with visual disabilities, who also showed higher glare sensitivity and adaptation problems related to non-uniform lighting. The latter ones are also highly related to the conditions in physiotherapy centres, where, in particular, elderly people with an increased risk of age-related visual defects, are likely to be present.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, about one-third of the employees were dissatisfied with artificial light and the overall quality of light, and two out of five of those having a window were dissatisfied with their view. Hauck et al , 48 in their test comparing the visual performance of visually impaired and normal-sighted individuals, found that special lighting conditions were required by most people with visual disabilities, who also showed higher glare sensitivity and adaptation problems related to non-uniform lighting. The latter ones are also highly related to the conditions in physiotherapy centres, where, in particular, elderly people with an increased risk of age-related visual defects, are likely to be present.…”
Section: Introductionmentioning
confidence: 99%
“…Avaliando as necessidades de iluminação do indivíduo com perdas visuais, é possível combinar auxílios visuais com estratégias de iluminação para tarefas específicas do dia a dia como: ler e escrever (Munford, 2004); preparar e servir comida (Brunnström et al, 2004); determinar a cor da roupa e mover-se em um ambiente (Barstow et al, 2011); ver-se no espelho, colocar o plugue na tomada e a chave na fechadura da porta (Butler et al, 2019); entre outras. Condições de iluminação desfavoráveis podem dificultar ainda mais a visão residual dos indivíduos com perdas visuais (Hauck et al, 2019). b) Superfície e diferenciação do piso.…”
Section: Iluminação E Baixa Visãounclassified